2018
DOI: 10.1002/cbdv.201800183
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Cytotoxic and Antibacterial Activities of Essential Oils of Cultivated Clones of Juniperus communis and Wild Juniperus Species

Abstract: Needles of seven cultivated clones (C1 – C7) of Juniperus communis at lower altitude and three wild Juniperus species (J. communis, J. recurva and J. indica) at higher altitudes were investigated comparatively for their essential oils (EOs) yields, chemical composition, cytotoxic and antibacterial activities. The EOs yields varied from 0.26 to 0.56% (v/w) among samples. Sixty‐one volatile components were identified by gas chromatography‐mass spectrometry (GC/MS) and quantified using gas chromatography GC (FID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Data are the mean AE SD of three experiments *P < 0Á05, **P < 0Á01, ***P < 0Á001, ****P < 0Á0001 vs DMSO. [Colour figure can be viewed at wileyonlinelibrary.com] with a-pinene, the main component in all researches considered (Cabral et al 2012;Maurya et al 2018;Vasilijevi c et al 2018). Moreover, our EO of J. communis resulted more cytotoxic than J. scopulorum and J. horizontalis EOs, probably due to the presence of a-pinene (67-80%), reported as an apoptotic and antimetastatic compound (Matsuo et al 2011), that instead was present in very low percentages in the other two EOs (2Á3-13%).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Data are the mean AE SD of three experiments *P < 0Á05, **P < 0Á01, ***P < 0Á001, ****P < 0Á0001 vs DMSO. [Colour figure can be viewed at wileyonlinelibrary.com] with a-pinene, the main component in all researches considered (Cabral et al 2012;Maurya et al 2018;Vasilijevi c et al 2018). Moreover, our EO of J. communis resulted more cytotoxic than J. scopulorum and J. horizontalis EOs, probably due to the presence of a-pinene (67-80%), reported as an apoptotic and antimetastatic compound (Matsuo et al 2011), that instead was present in very low percentages in the other two EOs (2Á3-13%).…”
Section: Discussionmentioning
confidence: 80%
“…Our results showed that J. communis EO has a stronger cytotoxic activity than the other two tested EOs, with 81% cell death after a treatment with 100 µg ml À1 for 24 h. Few studies reported the cytotoxicity of J. communis EO on different cell lines, but no studies have been carried out to verify the cytotoxicity of J. scopulorum and J. horizontalis EOs on neuroblastoma or other cell lines. Maurya et al (2018) demonstrated that the EO from fresh needles of J. communis from India was weakly cytotoxic against SiHa, A549 and A431 cell lines with IC 50 values of 150Á6, 134Á4 and 98Á0 lg ml À1 , after a treatment of 48 h, respectively. Vasilijevi c et al (2018) reported an IC 50 of 120 and 69Á4 lg ml À1 against MRC-7 and A549 cell lines after a treatment of 24 h with the EO from seed cones J. communis var.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Anti-infectious (Razi, 2008) Fumigation (Razi, 2008) Antibacterial (Maurya et al, 2018) α-pinene, limonene, sabinene (Maurya et al, 2018) Laurus nobilis L., Lauraceae; fruit…”
Section: Abhalmentioning
confidence: 99%